ANALISIS PRODUKTIVITAS KERJA AGEN UNIT PEMASARAN SYARIAH PADA PT. ASURANSI JIWA SYARIAH BUMIPUTERA CABANG MEDAN - Feri Wijaya; Zuhrinal. M. Nawawi; Wahyu Syarvina (EKSYA : Jurnal Ekonomi Syariah, 2023)
The purpose of this research is to find out how to increase marketing in agent work productivity in order to increase the target customers that have been determined at PT. Bumiputera Sharia Life Insurance Medan Branch and agent work productivity analysis at PT. Bumiputera Sharia Life Insurance, Medan Branch. This study used a qualitative method using data collection techniques in the form of interviews and documentation. The results of this study indicate that the marketing strategy carried out by PT AJS Bumiputera Medan Branch to increase agent productivity is to provide training to each agent regarding products, consolidate and remuneration every year, and conduct product visits and stabilization. Analysis of the productivity of PT AJS Bumiputera Medan Branch agents after analysis was still relatively low. This can be seen from that the Senior Executive Agent produced 100 customers. The Senior Agent shows the number 61 which means that each Senior Agent will produce 61 customers. Junior Agent shows the number 44 which means that each Junior Agent will produce 44 customers